Developing some Strategic Options to Remedy Organizational Derailment - Haider Jassim Al-Jiboury; Osam Karim Abd-Al-Hassan (مجلة الغري للعلوم الاقتصادية والادارية)
The study deals with strategic options as an independent variable through the option of self-awareness, executive training, feedback, leadership training, and organizational derailment as a dependent variable through its interpersonal problems, difficulty in team leadership, difficulty of change or adaptation and failure to achieve objectives. The study is to conduct in the Department of Health of Najaf. The study community consists of two hundred and thirty employees. The researcher relies on questionnaire form as a tool for data collection. Hundred and sixty questionnaires are distributed and hundred thirty three answers are retrieved for analysis. The sample in the population was represented by (58%). The research includes two hypotheses to test correlation and impact relationship. The statistical program (SPSS.V.20) is used to analyze the results, and the research comes to accept all hypotheses and concludes that the organization's awareness of the importance of strategic options and its role in remedy remedy many negative situations have a clear effect in reducing negative derailment. However, not achieving the objective required by the organization investigated due to non-interaction with its external environment. The research also recommends the need to adopt clear and valid strategies for achieving the objectives set, and this is by moving away from the development of plans away from reality and the use of skills and capabilities with the potential to develop solutions and address causes.